Two binding sites for [3H]PBR28 in human brain: implications for TSPO PET imaging of neuroinflammation - Owen,DR; Howell,OW; Tang,SP; Wells,LA; Bennacef,I; Bergstrom,M; Gunn,RN; Rabiner,EA; Wilkins,MR; Reynolds,R; Matthews,PM; Parker,CA (J Cereb Blood Flow Metab, 2010)
[(11)C]PBR28, a radioligand targeting the translocator protein (TSPO), does not produce a specific binding signal in approximately 14% of healthy volunteers. This phenomenon has not been reported for [(11)C]PK11195, another TSPO radioligand. We measured the specific binding signals with [(3)H]PK11195 and [(3)H]PBR28 in brain tissue from 22 donors. Overall, 23% of the samples did not generate a visually detectable specific autoradiographic signal with [(3)H]PBR28, although all samples showed [(3)H]PK11195 binding. There was a marked reduction in the affinity of [(3)H]PBR28 for TSPO in samples with no visible [(3)H]PBR28 autoradiographic signal (K(i)=188+/-15.6 nmol/L), relative to those showing normal signal (K(i)=3.4+/-0.5 nmol/L, P<0.001). Of this latter group, [(3)H]PBR28 bound with a two-site fit in 40% of cases, with affinities (K(i)) of 4.0+/-2.4 nmol/L (high-affinity site) and 313+/-77 nmol/L (low-affinity site). There was no difference in K(d) or B(max) for [(3)H]PK11195 in samples showing no [(3)H]PBR28 autoradiographic signal relative to those showing normal [(3)H]PBR28 autoradiographic signal. [(3)H]PK11195 bound with a single site for all samples. The existence of three different binding patterns with PBR28 (high-affinity binding (46%), low-affinity binding (23%), and two-site binding (31%)) suggests that a reduction in [(11)C]PBR28 binding may not be interpreted simply as a reduction in TSPO density. The functional significance of differences in binding characteristics warrants further investigation.